Antiulcer properties of essential oil and polypeptide K isolated from Momordica charantia L. seeds - Abu Bakar, Nurul'ain (2015)
Momordica charantia L. or bitter gourd, a Cucurbitaceae family plant is a plant native to the semi-tropical climate of Thailand, Asia, India and Africa and has been traditionally used as a folk remedy and best known for its anti-diabetic, antiinflammatory, anti-microbial, anti-ulcer and antihelmintic properties. The aims of this study were to investigate the anti-ulcerogenic activities of Momordica charantia L. (MC) essential oil and polypeptide k on various rats model. The anti-ulcerogenic effects of MCEO and polypeptide k were studied against HCl/Ethanol and Indomethacin-induced ulcer in rats. Spraque Dawley rats were given treatment orally for 7 days consecutively. In pre-treatment for MCEO, total length for HCl/EtOH is significantly longer than indomethacin Generally, for negative control, total length is 48.2±19.9. Supplementation with 10 MCEO, it reduced to 19.3±13.1 and similar to Rantidine 100 mg/kg. When the dose was increased, the total length was decreased (19.3±13.1 to 6.2±6.2). Rantidine 100 mg/kg as reference drug reduced the length about half of the negative control group. Furthermore, polypeptide k showed significantly longer (ulcer length) in HCl/EtOH than indomethacin. Generally, for negative control, total length is 43.0±14.1. Supplementation with 10 PPK, it reduced to 29.3±18.6 and slightly similar to Rantidine 100 mg/kg. When the dose was increased, the total length was decreased (29.3±18.6 to 13.6±9.5). Rantidine 100 mg/kg as reference drug reduced the length about half of the negative control group (22.1±13.2). This has been supported by findings from pylorus-ligated model in rats. Pre-treatment with MCEO at 10 mg/kg, 50 mg/kg and 100 mg/kg failed to increase the volume of gastric acid secretion when compared to control group. However, it significantly elevates the pH but not decrease the total acidity. Basically, MCEO managed to preserve the gastric wall by significantly increased the gastric wall mucus content. Polypeptide K (PPK) on the other hand, exerted a significant reduction in the total ulcer area (mm2) similarly with Ranitidine and successfully preserve the gastric wall by significantly increase the gastric wall mucus. However, it did not elevate the pH nor decrease the total acidity. As a conclusion, MCEO and polypeptide k possesses anti-ulcer effects in various ulcer models of rats.